Respons Pertumbuhan Anthocephalus cadamba (Roxb.) Miq. terhadap Penambahan Pupuk Kandang dan Arang Bambu di Kebun Raya Institut Teknologi Sumatera - Faradila Mei Jayani; Arief Juniarto (Journal of Science and Applicative Technology, 2021)
The loss of biodiversity in Indonesia is triggered by a decline in forest area. Institut Teknologi Sumatera (ITERA) in collaboration with the Indonesian Institute of Sciences (LIPI) conducts the development of the ITERA Botanical Gardens having an important role as the ex-situ conservation of flora. Reforestation activities are carried out to support the vegetation development in the botanical garden. This activity have to concern in fertilizer needs and soil ameliorant, especially in soil characteristic of ITERA botanical garden. The aim of this research is to analyze combinations of manure and bamboo biochar having the abitily to increase optimal growth of Anthocephalus cadamba (Roxb.) Miq. in ITERA Botanical Garden. The experimental design used in this research was Completely Randomized Design. The addition of manure and bamboo biochar increased height, diameter, and number of leaves of A. cadamba. The addition of 3 kg manure and 100 g bamboo biochar (B3) was the best treatment to increased height, diameter, and number of leaves of A. cadamba during 12 weeks of observation.